Leflunomide in complex treatment for rheumatoid arthritis - Yu A Olyunin; Yu A Olyunin (Современная ревматология)
It is noted that within recent years the severity of rheumatoid arthritis has noticeably diminished, as evidenced by the studies performed. This transformation is largely caused by the emergence of new first-line anti-inflammatory drugs (FLAIDs), leflunomide (LF, Arava) in particular. The experience gained during its 10-year wide clinical application shows that LF is as good as with methotrexate (MT) in the therapeutic potential and tolerance and supposedly can compare well with this agent in future. LF provides a significant clinical improvement in much earliest periods and has a more positive effect on patients 'functional status than MT. LF slows down articular destruction to a greater extent than MT given in combination with folic acid. By and large LF is well tolerated and causes adverse reactions less frequently than other FLAIDs.